Mining students' characteristics and effects on University preference choice : a case study of applied marketing in higher education. - Jasser, Muhammed Basheer; Sidi, Fatimah; Mustapha, Aida; Binhamid, Abdulelah Khaled T. (Foundation of Computer Science, 2013)
University servers and databases store a huge amount of data including personal details, registration details, evaluation assessment, performance profiles, and many more for students and lecturers alike. Mining such data offers a huge potential in advancing the educational field in the country because data mining is able to extract important models and hidden patterns beneath the data, which will help in decision-making to improve the outcome of educational establishments. This work concerns with data related to students. Understanding the characteristics of students enrolled in the university is important as it helps the university or institution to strategize on marketing their education programmes. This paper analyzes the student characteristics of Universiti Putra Malaysia based on their preference choice during registration at the university. The experiments are carried out using the Oracle Data Miner software and the results are analyzed and discussed.